2020
DOI: 10.1038/s42003-020-1077-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of molecular subtypes and clonal selection during establishment of patient-derived tumor xenografts from gastric adenocarcinoma

Abstract: Patient-derived xenografts (PDX) have emerged as an important translational research tool for understanding tumor biology and enabling drug efficacy testing. They are established by transfer of patient tumor into immune compromised mice with the intent of using them as Avatars; operating under the assumption that they closely resemble patient tumors. In this study, we established 27 PDX from 100 resected gastric cancers and studied their fidelity in histological and molecular subtypes. We show that the establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…This finding can be attributed to expansion of select cell populations in mice during PDX establishment, or sampling bias due to intra-tumoral heterogeneity. As a consequence, certain variants are observed at a higher frequency in PDX than the parental tumors, which is suggestive of engraftment-related clonal selection within PDX, as observed previously (Peille et al , 2020). For example, NF1 and SUZ12 were mutated only in the PDX line of MN-2, but not in the parental tumor.…”
Section: Resultssupporting
confidence: 82%
“…This finding can be attributed to expansion of select cell populations in mice during PDX establishment, or sampling bias due to intra-tumoral heterogeneity. As a consequence, certain variants are observed at a higher frequency in PDX than the parental tumors, which is suggestive of engraftment-related clonal selection within PDX, as observed previously (Peille et al , 2020). For example, NF1 and SUZ12 were mutated only in the PDX line of MN-2, but not in the parental tumor.…”
Section: Resultssupporting
confidence: 82%
“…33 This study found that diffuse-type tumors and low tumor cell percentages were associated with poor engraftment. Another study attempted to generate PDXs from 100 gastric tumors, successfully generating 27 PDXs, which were more likely intestinal histology, CIN subtype, and MSI-H. 34 Finally, a collection of 100 gastric cancer PDXs generated from 349 tumors was recently reported (28.7% success rate). 35 Again, histologic type and MSI-H status were associated with engraftment, as well as advanced stage and high RTK/RAS copy-number variation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mosaicism detection in cancer mainly used BAFSegmentation, TAPS, PICNIC, GISTIC and CNAG relating acute myeloid leukemia [ 234 ], hyperdiploid childhood acute lymphoblastic leukemia [ 235 ], ossification of fibromyxoid tumors [ 236 ], gastric adenocarcinoma [ 237 ], hepatoblastoma [ 238 ], lymphoblastic leukemia [ 239 ] and non-Hodgkin B-cell lymphoma [ 240 ]. Also, mosaicism genotyping was performed with MoChA, MAD, BAFSegmentation and PICNICfor mastocytosis [ 241 ] and drug resistance.…”
Section: Recent Studies Applying Inference Methods Of Snp Datamentioning
confidence: 99%